Functional black hard coating and preparation method thereof

The single-structure nitrogen, aluminum, and titanium black coating is generated through arc evaporation technology, which solves the problems of high cost and high process temperature of existing multi-layer structure coating equipment, and realizes the preparation of high hardness and high blackness single-layer coatings with low cost and low temperature processes.

CN119876864APending Publication Date: 2025-04-25DAI LIN TECHNOLOGY (SUZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510062325.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing decorative black coatings are mostly multi-layer structures, with high equipment costs and high process temperatures, a small range of suitable substrates, and the multi-layer structure increases the risk of binding force failure.

Method used

Arc evaporation technology is used to react aluminum-titanium targets with nitrogen to form a single structure nitrogen-aluminum-titanium black coating. The process temperature is 200-350℃, which is suitable for any shape of substrates.

Benefits of technology

A single-layer nitrogen aluminum-titanium black coating was prepared by low-cost and low-temperature processes, with a hardness of more than 20GPa and excellent blackness value, which solved the problems of high equipment costs and high process temperature in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876864A_ABST
    Figure CN119876864A_ABST
Patent Text Reader

Abstract

The invention discloses a functional black hard coating and a preparation method thereof, and the functional black hard coating is obtained by reacting an aluminum-titanium target material with nitrogen through an electric arc evaporation method to generate a black coating. According to the method, the titanium-aluminum target material is combined with relatively low current and a weak magnetic field, the reaction temperature and energy of the surface of the base material are reduced, the coating temperature is relatively low, a single coating structure is obtained, the method is suitable for base materials of any shape, the formed coating structure is similar to a columnar structure, and the columnar structure is a nanoscale rough structure and is difficult to reflect after being illuminated; and the black appearance can be realized. According to the invention, while the binding force is ensured, the coating structure is simplified, the thickness design is thin, the hardness can reach more than 20 GPa or even 30 GPa, the key blackness value is excellent, and the problem that a multi-layer black coating is prepared by adopting high-temperature and complex equipment in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to advanced material technology and relates to a functional coating, specifically a functional black hard coating and a preparation method thereof. Background Art

[0002] Surface engineering technology was born to meet the requirements of high wear resistance, heat resistance, corrosion resistance and other properties on the surface of materials. It is a universal engineering technology formed by the mutual penetration and integration of various disciplines. Hard coating is a coating used to increase the surface hardness of materials, mainly including DLC ​​(diamond-like carbon) coating, titanium nitride coating (TiN), Ta-c (colorful coating), chrome coating, nickel coating, among which DLC coating is also called diamond-like coating, a metastable amorphous material composed of carbon elements, similar to diamond in nature, and a material with a graphite atomic composition structure. It is an amorphous film with a gray-black color as the main color. DE3639469 describes a decorative black hard material coating, which also has high wear resistance. This hard material coating comprises a first layer composed of an element in the periodic table IVa or Va, a second layer containing a nitride of the element constituting the first layer, a third layer containing a carbide of the element, and a protective layer composed of a hard carbon layer, wherein small crystal particles of carbide of the element are buried in the protective layer. EP2959032 describes a decorative deep black coating based on a diamond-like coating, prepared by combining magnetron sputtering and plasma-assisted chemical vapor deposition, generally using a three-layer structure, namely a metal bonding layer, a metal carbide layer and a diamond-like layer, wherein the diamond-like layer has a thickness greater than 0.5 micrometers, a hardness between 15 and 20 GPa, a refractive index between 2 and 3, a neutral gray value L between 45 and 55, an intermediate layer thickness greater than 300 nanometers, and a hardness greater than 8 GPa. DE102013006317 discloses a multi-layer composite structure coating, in which copper, nickel, chromium layers and diamond-like carbon layers are applied in sequence on a substrate, wherein the copper and nickel coatings are 8 to 10 microns thick, the chromium is 0.5 microns, and the diamond-like carbon is 2 to 10 microns thick. The coated object has a glossiness ranging from matte to high gloss.

[0003] So far, decorative black coatings are all multi-layer structures, at least three layers, prepared by different technologies (electroplating, sputtering, chemical vapor deposition or plasma-assisted chemical vapor deposition). The disadvantages of existing technologies include: the hybrid technology has high requirements for coating equipment and high equipment cost; for chemical vapor deposition, the process temperature is high, between 700℃ and 900℃, and the applicable substrate range is small; the multi-layer coating structure, at least three layers, increases the risk of failure of the bonding force between the coatings; plasma-assisted chemical vapor deposition has high requirements for the substrate shape and limited loading capacity. Summary of the invention

[0004] In the prior art, decorative black coatings are all multi-layer structures, which have high requirements for coating equipment, high equipment cost, and high process temperature. The present invention discloses a functional black hard coating and a preparation method thereof, which uses arc evaporation technology, uses aluminum-titanium target materials, and reacts with nitrogen to generate a single-structure nitrogen-aluminum-titanium black coating. The coating temperature is relatively low, and the single coating structure is suitable for substrates of any shape. In addition, while ensuring the bonding strength, the coating structure is simplified, the thickness is designed to be thin, and the hardness can reach more than 20GPa or even 30GPa. Most importantly, the blackness value is excellent, which solves the problem of using high temperature and complex equipment to prepare multi-layer black coatings in the prior art.

[0005] The present invention adopts the following technical scheme.

[0006] A method for preparing a functional black hard coating comprises the following steps: using an aluminum-titanium target material through an arc evaporation method to react with nitrogen to generate a black coating, thereby obtaining a functional black hard coating.

[0007] A method for preparing a functional black hard coating composite comprises the following steps: using an aluminum-titanium target material through an arc evaporation method to react with nitrogen on the surface of a substrate to generate a black coating, thereby obtaining a functional black hard coating composite material consisting of a substrate and a functional black hard coating on its surface.

[0008] The invention discloses a functional black hard coating or a functional black hard coating composite prepared according to the preparation method.

[0009] In the present invention, the functional black hard coating has a single-layer structure.

[0010] In the present invention, the thickness of the functional black hard coating is less than 15 microns; preferably, the thickness of the functional black hard coating is less than 10 microns; preferably, the thickness of the functional black hard coating is less than 8 microns; preferably, the thickness of the functional black hard coating is less than 6 microns; preferably, the thickness of the functional black hard coating is 0.1 to 5 microns; preferably, the thickness of the functional black hard coating is 0.5 to 5 microns; preferably, the thickness of the functional black hard coating is 1 to 5 microns; preferably, the thickness of the functional black hard coating is 2 to 5 microns; preferably, the thickness of the functional black hard coating is 3 to 4.5 microns. The thickness of the functional black hard coating of the present invention is thin, and can be 1 micron, 2 microns, 3 microns, 4 microns, 5 microns or any thickness therein. Production tests have confirmed that the present invention achieves excellent mechanical properties with thin layers and single-layer coatings, and especially unexpectedly achieves good black effects.

[0011] In the present invention, in the aluminum-titanium target material, the molar ratio of titanium to aluminum is (3-7):(3-7), such as 70:30, 50:50, 33:67, or any ratio within the range.

[0012] In the present invention, the arc evaporation method is carried out in the presence of an inert gas, wherein the inert gas includes argon, helium, neon and the like.

[0013] In the present invention, the flow rate ratio of the inert gas to the nitrogen is (3-5): (5-15); preferably, the flow rate ratio of the inert gas to the nitrogen is (3-5): (8-10).

[0014] In the present invention, during arc evaporation, the current is 100-180A, the bias voltage is 10-30V, and the time is 80-250 minutes; preferably, during arc evaporation, the current is 120-160A, the bias voltage is 15-30V, and the time is 100-200 minutes; further preferably, during arc evaporation, the current is 130-150A, the bias voltage is 15-25V, and the time is 130-170 minutes.

[0015] Different from the prior art which uses heaters to achieve temperatures exceeding 450°C, mostly to 500°C, in the arc evaporation method of the present invention, no heater is required for heating, etching, and coating. The process temperature is 200-350°C through current and voltage. The formation mechanism of the black coating is different from that of the traditional arc evaporation nitrogen-aluminum-titanium coating. It uses titanium-aluminum target materials at relatively low current and weak magnetic field to reduce the reaction temperature and energy on the surface of the substrate. The coating structure formed is similar to a columnar structure. The columnar structure is a rough structure at the nanoscale and is difficult to reflect after exposure to light, which is conducive to achieving a black appearance.

[0016] In the present invention, the substrate is subjected to surface treatment. Preferably, the surface treatment comprises metal ion etching treatment and plasma etching treatment, preferably plasma etching treatment.

[0017] In the present invention, during the plasma etching process, hydrogen and an inert gas are used to generate plasma, wherein the inert gas includes argon, helium, neon, etc.

[0018] Preferably, the flow rate ratio of hydrogen to inert gas is (1-5): (1-3); more preferably, the flow rate ratio of hydrogen to inert gas is (2-4): (1-2).

[0019] In the present invention, during plasma etching treatment, the current is 100-200A, the bias voltage is 50-200V, and the time is 10-70 minutes; preferably, during plasma etching treatment, the current is 120-180A, the bias voltage is 70-150V, and the time is 20-60 minutes; further preferably, during plasma etching treatment, the current is 140-160A, the bias voltage is 80-120V, and the time is 30-50 minutes.

[0020] In the present invention, the plasma etching process is preheated. Preferably, the preheating is performed in an inert gas, wherein the inert gas includes argon, helium, neon, etc.

[0021] In the present invention, during the preheating treatment, the current is 100-200A and the time is 30-90 minutes; preferably, during the preheating treatment, the current is 120-180A and the time is 40-80 minutes; further preferably, during the preheating treatment, the current is 140-160A and the time is 50-70 minutes.

[0022] In the present invention, the substrate is a conventional product, and its material and shape are not limited, and do not affect the understanding of the technical effect of the present invention by those skilled in the art. The coating temperature of the present invention is relatively low, and the single coating structure is suitable for substrates of any shape. As an example, the substrate can be a pure metal, such as titanium (Ti), zirconium (Zr), aluminum (Al), vanadium (V), chromium (Cr), molybdenum (Mo), tungsten (WC), cobalt (Co), nickel (Ni), niobium (Nb), ruthenium (Ru), rhodium (Rh), tantalum (Ta), iridium (Ir), palladium (Pd), platinum (Pt), copper (Cu) gold (Au), silver (Ag), iron (Fe); it can be an alloy, including stainless steel or aluminum alloy, such as austenitic chromium-nickel-manganese alloy (200 series stainless steel), austenitic chromium-nickel alloy (300 series stainless steel), ferrite and martensitic chromium alloy (400 series stainless steel), heat-resistant chromium alloy (500 series stainless steel).

[0023] The invention discloses the application of the functional black hard coating or the functional black hard coating composite as or in the preparation of a black product.

[0024] In the present invention, the black product refers to a variety of materials in this field, which can be selected according to the substrate, including molds, medical devices, knives, auto parts, machine tools, electronic components, decorative materials (hardware decorative parts), etc.

[0025] The invention discloses a black material, comprising the above-mentioned functional black hard coating or the functional black hard coating composite.

[0026] In this field, black is defined by L value and a and b. The lower the L value, the better, and a and b are as close to 0 as possible. Diamond-like coatings are currently used in high-end decoration in the commercial industry, but its L value is >40, a=1, b=3. It is difficult to find a coating with an L value less than 40 in the prior art, which can replace the traditional diamond-like coating. Aluminum titanium nitride coating is a new type of coating that has appeared in recent years. The color of related products currently on the market is not black, but mainly purple-gray and purple-brown, and cannot be used in some production ends with high blackness requirements. The present invention processes the surface of a cheap substrate material to obtain a multifunctional surface. The surface coating or modified layer is very thin, less than 8 microns or even less than 5 microns, but it has an effect that is difficult to achieve with a large amount of expensive overall materials. The present invention greatly saves materials, energy, and resources. After pre-protection, parts and components can withstand corrosion, wear and high temperature, so that the service life of the components is greatly improved. For example, the service life of parts (or tools) is greatly improved after treatment; in particular, the present invention adopts titanium aluminum target material, at relatively low current and weak magnetic field, to reduce the reaction temperature and energy of the substrate surface, and the coating structure formed is similar to a columnar structure. The columnar structure is a nano-scale rough structure, which is difficult to reflect after exposure to light, which is conducive to achieving a black appearance, and the L value is less than 40. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure of an existing publicly available decorative black coating; 1 is a substrate, 2 is a metal layer, 3 is a metal carbide layer, 4 is a diamond-like layer, 5 is a copper metal layer, 6 is a nickel metal layer, 7 is a chromium metal layer, and 8 is a diamond-like layer.

[0028] Figure 2 This is a schematic diagram of the structure of the black decorative coating disclosed in the present invention, 1 is a substrate, and 2 is a nitrogen-aluminum-titanium coating.

[0029] Figure 3 This is a photo of the appearance of the functional black hard coating composite.

[0030] Figure 4 The black titanium nitride aluminum Ti 0.33 Al 0.67 N coating adhesion under microscope, HF1.

[0031] Figure 5 The black titanium nitride aluminum Ti 0.33 Al 0.67 N coating structure under microscope.

[0032] Figure 6 Black Nitride Aluminum Titanium Ti is measured by scanning electron microscope 0.33 Al 0.67 N is the thickness of the coating.

[0033] Figure 7 The existing method is nitrogen aluminum titanium Ti0.33 Al 0.67 Microscopic coating structure of N coating.

[0034] Figure 8 The existing method is nitrogen aluminum titanium Ti 0.33 Al 0.67 SEM cross-sectional image of N coating.

[0035] Fig. 9 Ti in Comparative Example 2 0.33 Al 0.67 Microscopic binding force diagram of N coating, HF6.

[0036] Fig.10 For comparative example 3, nitrogen aluminum titanium Ti 0.33 Al 0.67 N coating visual results. DETAILED DESCRIPTION

[0037] In the prior art, decorative black coatings are all multi-layer structures, see Figure 1 , is a schematic diagram of the decorative black coating previously disclosed, Figure 1 A is the coating structure mentioned in EP2959032, 1 is the substrate, 2 is the metal layer, 3 is the metal carbide layer, 4 is the diamond-like carbon layer, Figure 1 B is the multilayer structure mentioned in DE102013006317, 1 is a substrate, 5 is a copper metal layer, 6 is a nickel metal layer, 7 is a chromium metal layer, and 8 is a diamond-like carbon layer.

[0038] The existing technology has high requirements for coating equipment, high equipment cost, and high process temperature.

[0039] The present invention discloses a functional black hard coating and a preparation method thereof, wherein an aluminum-titanium target material is used to react with nitrogen to form a single-structure nitrogen-aluminum-titanium black coating by arc evaporation technology, see Figure 2 , is the black decorative coating structure disclosed in the present invention, 1 is a substrate, 2 is a nitrogen aluminum titanium coating; the coating temperature of the present invention is relatively low, a single coating structure is suitable for substrates of any shape, and while ensuring the bonding strength, the coating structure is simplified, the thickness is designed to be thin, the hardness can reach more than 20GPa or even 30GPa, and most importantly, the blackness value is excellent, which solves the problem of the prior art using high temperature and complex equipment to prepare multi-layer black coatings.

[0040] The present invention discloses a single coating technology, that is, using traditional arc evaporation equipment, the coating temperature is relatively low, the single coating structure is suitable for substrates of any shape. Specifically, the present invention discloses an arc evaporation technology coating process, the process temperature is 200-350°C, the single coating structure can process substrates of any shape. It has the following advantages: First, the arc evaporation technology is used, the coating equipment structure is simple and the cost is low; second, the process temperature is suitable for most substrates and can process substrates of any shape; third, the arc evaporation process has a high ionization rate and good bonding force; fourth, the process can achieve black decorative functional coatings using a single-layer structure.

[0041] The present invention adopts arc evaporation technology, uses aluminum-titanium target material, and reacts with nitrogen to generate a single-structure nitrogen-aluminum-titanium black coating. Figure 2 As shown, the nitrogen aluminum titanium black coating is directly deposited on the substrate as the first layer (the only layer); the formation of the black coating of the present invention is different from the traditional arc evaporation nitrogen aluminum titanium coating. It uses a titanium aluminum target material, and at a relatively low current and a weak magnetic field, reduces the reaction temperature and energy on the surface of the substrate. The coating structure formed is similar to a columnar structure, which is a nano-scale rough structure. These structures are conducive to achieving a black appearance, and the L value is less than 40.

[0042] The present invention adopts arc evaporation process for coating deposition, the process temperature is 250 to 350°C, and while ensuring the bonding force, the coating structure is simplified, and the thickness can be 2 to 5 microns, preferably 3 to 4 microns. A Ti / Al target material is used (the titanium and aluminum components can be selected as one or a mixture of 70 / 30, 50 / 50, 33 / 67), the target weight can be selected from 400 to 800 grams, the gas is nitrogen, and the etching can be metal ion etching or plasma etching.

[0043] As an example, using an existing arc evaporation device (including a cathode located on the left side of a chamber, a plasma generation chamber located on the upper part of the chamber, an anode, a rotating large disk located on the left side of the chamber, a substrate (disk-shaped, round-shaped, rod-shaped, etc.) placed on the large disk or a fixture, a vacuum system connected to the bottom of the chamber, and a magnetic coil); the method for preparing a functional black hard coating (composite material) of the present invention includes the following steps, (1) Vacuum after loading the sample; (2) Heating and introducing inert gas; (3) Metal ion etching or plasma etching; (4) Al-Ti-N coating deposition: the inert gas flow rate is 300 to 500 sccm, the nitrogen flow rate is 800 to 1000 sccm, the Ti-Al target current is 120 to 160 A, the bias voltage is 10 to 20 V, and the time is 100 to 200 minutes; (5) After coating, ventilation and cooling are carried out.

[0044] In the above technical solution, step (1) and step (5) are prior arts, and the specific operations of step (2), step (3) and step (4) are conventional operations. The present invention preferably uses different process parameters.

[0045] For example, step (1) vacuuming: the substrate is placed on the tray, the chamber door is closed, and the vacuum system is pumped to 1-5x10 - 1 Pa, time 10 to 30 minutes.

[0046] For example, in step (2) heating, the large disk is rotated at a speed of 2 to 10 revolutions per minute, an inert gas Ar is introduced and the flow rate is controlled at 100 to 200 sccm, the ion source is turned on to utilize plasma heating, and the current density is 100 to 200 A. In actual production, the upper and lower coils are turned on at the same time to ensure uniform heating. This step takes 20 to 120 minutes. This step only utilizes plasma heating, omitting the heater conventionally used in the prior art.

[0047] For example, in step (5), after the deposition reaction in step (4) is completed, helium is routinely introduced for cooling.

[0048] In the above technical solution, in step (3), plasma etching is preferably used. Specifically, the substrate is treated with a plasma etching process using H2 and Ar before deposition, with an Ar gas flow rate of 100 to 200 sccm, a hydrogen gas flow rate of 200 to 400 sccm, a current controlled at 100 to 200 A, and an applied bias voltage of 100 to 200 volts for 10 to 60 minutes.

[0049] In the above technical solution, step (3) surface treatment is combined with step (4) deposition to ensure the bonding strength while simplifying the coating structure. The thickness can be 2 to 5 microns, preferably 3 to 4.5 microns. The thickness is designed to be thin, the surface quality is good, the hardness can reach above 20 GPa or even 30 GPa, and most importantly, the blackness value is excellent, which solves the problem of the prior art of using high temperature and complex equipment to prepare multi-layer black coatings.

[0050] The single structure nitrogen aluminum titanium coating used in the present invention obtains a black appearance and functional coating, and improves the bonding strength between the coating and the substrate. The following specific experiments illustrate the technical progress of the present invention, which is an example rather than a limitation. The raw materials used are conventional products, and the specific preparation operations and performance tests are all conventional technologies. Embodiment 1

[0051] On the existing conventional arc evaporation equipment, Ti / Al (33 / 67) target material is used, the target weight is 700 grams, and the target material is installed before the substrate enters the furnace; plasma etching is used; the substrate is bearing steel (100Cr6). Specifically: (1) Vacuuming: The substrate is loaded onto the large plate for rotation inspection. After the chamber door is closed, the vacuum system is pumped to 0.2 Pa for 20 minutes. (2) Heating: Rotate the disk at 3 rpm, introduce inert gas Ar with a flow rate of 150 sccm, turn on the ion source to use plasma heating, the current density is 150 A, and turn on the upper and lower coils at the same time to ensure uniform heating. This step takes 60 min. (3) Plasma etching: Before deposition, the substrate was cleaned by plasma etching using H2 and Ar. The argon gas flow rate was 100 sccm, the hydrogen gas flow rate was 300 sccm, the tungsten filament current was controlled at 150 A, and a bias voltage of 100 V was applied for 45 min. (4) Al-Ti-N coating deposition: turn off hydrogen, introduce inert gas Ar at a flow rate of 400 sccm, nitrogen at a flow rate of 1000 sccm, Ti-Al target current of 140 A, bias voltage of 20 V, and time of 150 min; (5) After coating, helium gas is used for cooling.

[0052] After coating, the samples were subjected to coating performance tests, mainly including coating adhesion, coating thickness, coating hardness, coating structure and color L*a*b value.

[0053] The appearance photos of the above functional black hard coating composite are shown in Figure 3 , the coating is tested as follows.

[0054] Adhesion is based on the coating adhesion industry standard VDI3198, substrate hardness 59HRc, coating adhesion HF1, adhesion is very good, see Figure 4 ; Figure 5 For observation under an optical microscope, magnification is 100 times, and the coating bevel is conventionally ground.

[0055] The coating thickness was directly measured by the cross-section method combined with a scanning electron microscope, see Figure 6 The total coating thickness is about 4 microns. At the same time, scanning electron microscopy also proves the formation of columnar coating structure.

[0056] The coating colors are as follows:

[0057] The coating hardness was measured at 25.8 GPa.

[0058] Comparative Example 1 The common nitrogen-aluminum-titanium coatings on the market are all mixed with titanium targets and Ti / Al (33 / 67) targets. On traditional arc evaporation equipment, Ti and Ti / Al (33 / 67) targets are used, the target weight is 700 grams, plasma etching is used, and the substrate is bearing steel (100Cr6). Referring to the existing technology, specifically: (1) Vacuuming: The substrate is loaded onto the large plate for rotation inspection. After the chamber door is closed, the vacuum system is pumped to 0.2 Pa for 20 minutes. (2) Heating: Rotate the large plate at 3 rpm, introduce inert gas Ar with a flow rate controlled at 150 sccm, turn on the heater and set the heater temperature to 500°C, turn on the ion source for plasma heating at a current density of 150 A, and turn on the upper and lower coils at the same time to ensure uniform heating. This step takes 60 min. (3) Plasma etching: Before deposition, the substrate was cleaned by plasma etching using H2 and Ar. The argon gas flow rate was 100 sccm, the hydrogen gas flow rate was 400 sccm, the tungsten filament current was controlled at 150 A, and the bias voltage was 60 V for 120 min. (4) Titanium coating deposition: turn off hydrogen, introduce inert gas Ar at a flow rate of 300 sccm, only turn on the titanium target and the titanium target current is 150 A, the bias voltage is 200 V, and the time is 5 minutes; (5) Al-Ti-N coating deposition: the inert gas Ar flow rate was 300 sccm, the nitrogen flow rate was 1000 sccm, only the Ti-Al target was turned on and the current was set to 150 A, the bias voltage was 100 V, and the time was 95 min; (6) After coating, helium gas is used for cooling.

[0059] The bonding strength is based on the coating bonding strength industrial standard VDI3198, the substrate hardness is 45HRc, the coating bonding strength is HF1, the bonding strength is good, Figure 7 For observation under an optical microscope, magnification was 100 times, the coating bevel was conventionally ground and the intermediate substrate was acid-etched in order to observe the titanium thin layer.

[0060] The coating thickness was directly measured by the cross-section method combined with a scanning electron microscope, see Figure 8 The total coating thickness is about 4.1 microns. At the same time, scanning electron microscopy shows the formation of a dense coating structure.

[0061] However, the coating prepared by this method is gray-black, and the coating color range is as follows:

[0062] Obviously, it is impossible to achieve a black coating by referring to the existing process for preparing the nitrogen aluminum titanium coating, and the addition of the titanium coating is to increase the bonding strength with the substrate.

[0063] Comparative Example 2 The titanium coating of comparative example 1 was removed, and other coating process parameters were retained. The bonding strength was poor according to the coating bonding strength industrial standard VDI3198, the substrate hardness was 45HRc, and the coating bonding strength was HF6. Fig. 9 For observation under an optical microscope, magnification was 100 times.

[0064] Similarly, the coating prepared by this method is gray-black, and the coating color range is as follows:

[0065] The color range of Comparative Example 2 is very close to that of Comparative Example 1, but due to the lack of titanium coating, the bonding strength is very poor and cannot be used commercially.

[0066] Comparative Example 3 On the existing conventional arc evaporation equipment, Ti / Al (33 / 67) target material is used, the target weight is 700 grams, and the target material is installed before the substrate enters the furnace; plasma etching is used; the substrate is bearing steel (100Cr6). Specifically: (1) Vacuuming: The substrate is loaded onto the large plate for rotation inspection. After the chamber door is closed, the vacuum system is pumped to 0.2 Pa for 20 minutes. (2) Heating: Rotate the disk at 3 rpm, introduce inert gas Ar with a flow rate controlled at 150 sccm, turn on the ion source for plasma heating, current density 200 A, and turn on the upper and lower coils at the same time to ensure uniform heating. This step takes 60 min. (3) Plasma etching: Before deposition, the substrate was cleaned by plasma etching using H2 and Ar. The Ar gas flow rate was 100 sccm, the hydrogen gas flow rate was 300 sccm, the tungsten filament current was controlled at 200 A, and the bias voltage was 150 V for 45 min. (4) Al-Ti-N coating deposition: the inert gas Ar flow rate is 400 sccm, the nitrogen flow rate is 1000 sccm, the Ti-Al target current is 140 A, the bias voltage is 80 V, and the time is 150 min; (5) After coating, helium gas is used for cooling.

[0067] After coating, the samples were subjected to coating performance tests, mainly including coating adhesion and color L*a*b values. 0.33 Al 0.67 N coating is gray, see the appearance photo Fig.10 , the coating is tested as follows.

[0068] The bonding strength is based on the coating bonding strength industrial standard VDI3198, the substrate hardness is 52HRc, the coating bonding strength is HF1, and the bonding strength is good.

[0069] The coating colors are as follows: Example 2 Black hard coating

[0070] On the existing conventional arc evaporation equipment, Ti / Al (33 / 67) target material is used, the target weight is 700 grams, and the target material is installed before the substrate enters the furnace; plasma etching is used; the substrate is bearing steel (100Cr6). Specifically: (1) Vacuuming: The substrate is loaded onto the large plate for rotation inspection. After the chamber door is closed, the vacuum system is pumped to 0.3 Pa for 15 minutes. (2) Heating: Rotate the disk at 3 rpm, introduce inert gas Ar with a flow rate of 150 sccm, turn on the ion source to use plasma heating, the current density is 150 A, and turn on the upper and lower coils at the same time to ensure uniform heating. This step takes 60 min. (3) Plasma etching: Before deposition, the substrate was cleaned by plasma etching using H2 and Ar. The argon gas flow rate was 100 sccm, the hydrogen gas flow rate was 300 sccm, the tungsten filament current was controlled at 150 A, and a bias voltage of 100 V was applied for 45 min. (4) Al-Ti-N coating deposition: turn off hydrogen, introduce inert gas Ar at a flow rate of 400 sccm, nitrogen at a flow rate of 1000 sccm, Ti-Al target current of 140 A, bias voltage of 25 V, and time of 150 min; (5) After coating, helium is passed for cooling and the product is black in appearance. Example 3 Black hard coating

[0071] On the existing conventional arc evaporation equipment, Ti / Al (33 / 67) target material is used, the target weight is 700 grams, and the target material is installed before the substrate enters the furnace; plasma etching is used; the substrate is bearing steel (100Cr6). Specifically: (1) Vacuuming: The substrate is loaded onto the large plate for rotation inspection. After the chamber door is closed, the vacuum system is pumped to 0.2 Pa for 20 minutes. (2) Heating: Rotate the disk at 3 rpm, introduce inert gas Ar with a flow rate of 150 sccm, turn on the ion source to use plasma heating, the current density is 150 A, and turn on the upper and lower coils at the same time to ensure uniform heating. This step takes 50 min. (3) Plasma etching: Before deposition, the substrate was cleaned by plasma etching using H2 and Ar. The argon gas flow rate was 100 sccm, the hydrogen gas flow rate was 300 sccm, the tungsten filament current was controlled at 145 A, and the bias voltage was 110 V for 45 min. (4) Al-Ti-N coating deposition: turn off hydrogen, introduce inert gas Ar at a flow rate of 400 sccm, nitrogen at a flow rate of 1000 sccm, Ti-Al target current of 145 A, bias voltage of 15 V, and time of 130 min; (5) After coating, helium is passed for cooling and the product is black in appearance.

[0072] The prior art uses arc evaporation to form a nitrogen-aluminum-titanium coating, but there are few black products and few reports; the technical solution of the present invention is to combine surface treatment with deposition to achieve excellent blackness. At present, the definition of black is L value and a, b. The lower the L value, the better, and a and b are as close to 0 as possible. At present, diamond-like is mainly used in commercial applications for high-end decoration, but its L value is >40, a=1, b=3, but the prior art has not found a coating with an L value less than 40 that can replace the traditional diamond-like coating. The present invention discloses a nitrogen-aluminum-titanium hard coating suitable for high-end decorative black coatings, which is prepared by arc evaporation technology. The black nitrogen-aluminum-titanium coating is a single-layer structure with a simple process and is not limited by the shape and size of the substrate. It greatly improves the bonding strength of the coating and is convenient for commercial production.

Claims

1. A method for preparing a functional black hard coating, comprising the following steps: using an aluminum-titanium target material through an arc evaporation method, reacting with nitrogen to generate a black coating, thereby obtaining a functional black hard coating.

2. A method for preparing a functional black hard coating composite material, comprising the following steps: using an aluminum-titanium target material through an arc evaporation method, reacting with nitrogen on the surface of a substrate to generate a black coating, thereby obtaining a functional black hard coating composite material.

3. The preparation method according to claim 1 or 2, characterized in that: In the aluminum-titanium target, the molar ratio of titanium to aluminum is (3-7): (3-7).

4. The preparation method according to claim 1 or 2, characterized in that: The arc evaporation method is carried out in the presence of an inert gas, and the flow rate ratio of the inert gas to nitrogen is (3-5): (5-15).

5. The preparation method according to claim 1 or 2, characterized in that: During arc evaporation, the current is 100 to 180 A, the bias voltage is 10 to 30 volts, and the time is 80 to 250 minutes.

6. The preparation method according to claim 1 or 2, characterized in that: The substrate is surface treated; the surface treatment includes metal ion etching and plasma etching.

7. The preparation method according to claim 6, characterized in that: During plasma etching, plasma is generated by using hydrogen and inert gas; the flow rate ratio of hydrogen and inert gas is (1-5): (1-3); during plasma etching, the current is 100-200A, the bias voltage is 50-200V, and the time is 10-70 minutes.

8. A functional black hard coating or a functional black hard coating composite prepared by the preparation method according to claim 1 or 2.

9. Use of the functional black hard coating or the functional black hard coating composite material according to claim 8 as or in the preparation of a black product.

10. A black material, comprising the functional black hard coating or the functional black hard coating composite according to claim 8.

Citation Information

Patent Citations

  • Method for producing a deep black appearance

    DE102013006317A1

  • Hard material layer with high wear resistance and decorative black intrinsic color Field of application of the invention

    DE3639469A1

  • Decorative, jet black coating

    EP2959032A1